Combined hysterectomy and mastectomy surgery for transgender patients in an integrated health care setting. Issue 4 (2nd October 2017) - Cizek, Stephanie; Nguyen, Nancy; Lyon, Liisa; Zaritsky, Eve; Weiss, Erica
ABSTRACT:   Background : Hysterectomy and mastectomy surgery for gender affirmation have traditionally been performed as separate surgeries. Our institution offers these surgeries as a single combined procedure, typically with same-day discharge. Decreasing the number of times patients need to have surgery may reduce barriers to care by limiting surgical and hospital stay events. Our primary objective was to describe the perioperative experience of transgender patients who underwent combined hysterectomy and mastectomy surgery. Methods : This retrospective case series assessed patients who underwent combined hysterectomy and mastectomy surgery between 2013 and 2015 in an integrated health care setting in the United States. Chart reviews were performed for outcomes of interest, which included operative and postoperative complications. Results : We identified 25 patients who underwent a combined hysterectomy and mastectomy for the indication of gender transition. Preoperative patient characteristics included a median age of 31, with a median BMI of 25. Ninety-two percent of the patients were on testosterone therapy at the time of surgery. A total of 76% and 24% of patients had laparoscopic and vaginal hysterectomies, respectively. Intraoperatively, the average blood loss was 104 mL, and there were no complications. Eighty percent of patients were discharged on the same day. Postoperatively, 92% of patients experienced no major complications. One patient received a uterine artery embolization and blood transfusion for postoperative intraabdominal bleeding, and one patient presented 9 weeks after surgery with partial vaginal cuff dehiscence requiring a cuff revision. There were no re-admissions within six months of surgery. There were no major mastectomy-related complications. Conclusions : Combined surgeries are feasible and reduce the number of surgical events and hospital stays. There were no complications that could be attributed to undergoing two procedures as a single incident.